Preparation method of wurtzite type boron nitride, wurtzite type boron nitride and regulation and control method of thermal conductivity of boron nitride
By using a diamond anvil device to convert hexagonal phase boron nitride into wurtzite type boron nitride under normal temperature and pressurization conditions, the high energy consumption problem of preparation under high temperature and high pressure in the prior art is solved, and a stable existence is achieved. Preparation of wurtzite boron nitride and thermal conductivity regulation.
Patent Information
- Application Number
- CN202411333997.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The existing preparation methods for wurtzite type boron nitride require high temperature and high pressure, resulting in high energy consumption and difficult production.
The diamond anvil device is used to convert the hexagonal phase boron nitride into wurtzite type boron nitride under normal temperature and pressurization conditions. The thermal conductivity and crystal phase are controlled by regulating the pressurized pressure, so as to achieve preparation without high temperature.
The energy consumption is reduced and the preparation process is simplified. The resulting wurtzite boron nitride is stable at room temperature and normal pressure, and is suitable for electronic devices with different heat dissipation efficiencies.
Smart Images

Figure CN119143088A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of boron nitride materials, and more specifically, to a method for preparing wurtzite boron nitride, and a method for regulating the thermal conductivity of wurtzite boron nitride and boron nitride. Background Art
[0002] Wurtzite boron nitride is a relatively rare boron nitride material with high hardness. The current preparation method of wurtzite boron nitride requires high temperature and high pressure preparation conditions, generally requiring a temperature of 1000 degrees Celsius or even 1500 degrees Celsius. Therefore, the energy consumption of producing wurtzite boron nitride is high and it is not easy to obtain. Summary of the invention
[0003] The present application is provided to solve the above defects in the prior art. A method for preparing wurtzite boron nitride, a method for regulating the thermal conductivity of wurtzite boron nitride and boron nitride is needed, which can prepare wurtzite boron nitride under the condition of only pressurization and no high temperature.
[0004] In a first aspect of the present application, a method for preparing wurtzite boron nitride is provided, the method comprising: using a diamond anvil cell apparatus, using hexagonal phase (hBN) boron nitride as a raw material, and preparing wurtzite (WBN) boron nitride at room temperature and under pressurized conditions, wherein the pressurized pressure is greater than or equal to 12 GPa.
[0005] In a second aspect of the present application, there is provided wurtzite boron nitride prepared by the method for preparing wurtzite boron nitride described in any embodiment of the present application.
[0006] The third aspect of the present application provides a method for regulating the thermal conductivity of boron nitride, using a diamond anvil cell device to process hexagonal boron nitride at room temperature and pressurized conditions to obtain a boron nitride product; by regulating the pressurized pressure, boron nitride with different thermal conductivities and different crystal phases is obtained, and the pressurized pressure is 0-50GPa.
[0007] The preparation method of wurtzite boron nitride, the method for regulating the thermal conductivity of wurtzite boron nitride and boron nitride provided in each embodiment of the present application use hexagonal boron nitride as a raw material and successfully prepare boron nitride containing wurtzite at room temperature and pressurized conditions using a diamond anvil cell. The preparation method overcomes the barrier that wurtzite boron nitride can only be obtained under high temperature and high pressure conditions, the method is easier to operate, and the obtained wurtzite boron nitride product can exist stably at room temperature and pressure and will not change back to hexagonal boron nitride. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.
[0009] Figure 1 The Raman spectrum of Example 1 of the present application during the process of increasing the temperature to 16.74 GPa is shown; Figure 2 The Raman spectrum of Example 1 of the present application during the process of increasing the temperature to 16.74 GPa is shown; Figure 3 The Raman spectrum of Example 1 of the present application during the decompression process after the pressure was increased to 16.74 GPa is shown; Figure 4 The thermal conductivity detection diagram of Example 1 of the present application during the process of increasing the pressure to 16.74 GPa is shown; Figure 5 The Raman spectra of hBN boron nitride with different mass numbers are shown. DETAILED DESCRIPTION
[0010] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.
[0011] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.
[0012] According to an embodiment of the present application, a method for preparing wurtzite boron nitride is provided, the method comprising: using a diamond anvil cell (DAC) device, using hexagonal boron nitride as a raw material, and preparing wurtzite boron nitride at room temperature and under pressurized conditions, wherein the pressurized pressure is greater than or equal to 12 GPa.
[0013] The diamond anvil device consists of a pair of diamond anvils and a metal sealing gasket. The sample and the standard pressure ruby are placed simultaneously in a sealed chamber formed by the diamond anvils. By rotating the anvils, a pressure of tens or even hundreds of gigapascals (GPa) is generated in the diamond pressure chamber.
[0014] Hexagonal boron nitride two-dimensional materials are more easily compressed due to weaker van der Waals forces between layers, and may even produce new physical properties due to interlayer bonding-induced phase transitions. Using a diamond anvil cell, hexagonal boron nitride is transformed into wurtzite (WBN) boron nitride at room temperature and under pressure.
[0015] In addition, through the reaction under room temperature and pressure conditions in the diamond anvil cell, the interlayer distance can be significantly shortened, the interlayer van der Waals interaction can be enhanced, and the effective regulation of the electronic energy band and phonon spectrum can be achieved. The thermal conductivity of the obtained WBN boron nitride is reduced, that is, during the pressurized reaction, the thermal conductivity increases before it turns into the WBN phase, and the thermal conductivity begins to decrease after the WBN phase begins to exist.
[0016] By using a diamond anvil cell device at room temperature and under pressure, the conversion process from hBN phase boron nitride to WBN phase boron nitride does not need to be carried out at high temperature, thus reducing energy consumption.
[0017] In some embodiments, the pressurized pressure is greater than or equal to 15 GPa. Under the condition that the pressurized pressure is greater than 11 GPa, the converted WBN phase gradually increases. Under the condition that the pressure is greater than 15 GPa, there is no hBN phase in the material and it is converted to WBN phase. The pressurized pressure can be [15-17] GPa, [17-20] GPa, etc. The maximum pressurized pressure is related to the diamond table area of the diamond anvil device, and generally can reach a maximum of 40-50 GPa. After experiments, as the pressure increases to more than 20 GPa, the WBN phase is still synthesized.
[0018] In some embodiments, the preparation method further comprises: plating a gold film on the surface of the hexagonal boron nitride, and placing the gold-plated sample into a chamber of a diamond anvil cell and subjecting it to a pressurized treatment.
[0019] In some embodiments, the preparation method further comprises: after the gold-plated sample is placed in a chamber of a diamond anvil cell, silicone oil is sealed in the chamber, so that the interior of the chamber meets the hydrostatic pressure requirement.
[0020] In some embodiments, the pressure is applied by rotating the diamond anvil, and the angle of each rotation is 30-60 degrees. The pressure in the chamber is gradually increased through multiple rotations.
[0021] In some embodiments, the thickness of the hexagonal boron nitride raw material is 60-80 nm. The hexagonal boron nitride of appropriate thickness is selected so that each position of the raw material is uniformly transformed into the WBN phase under pressure. In some embodiments, the raw material can be processed by tape stripping to obtain a sample with uniform number of layers and morphology.
[0022] In some embodiments, the thickness of the gold film is 60-80 nm. The gold film can be plated by a magnetron coating apparatus, and the coating rate can be controlled so that the sample surface is covered with a gold film of suitable thickness. The coating can also be performed by electron beam evaporation.
[0023] In some embodiments, after the pressurization treatment, the diamond anvil cell is depressurized to obtain wurtzite boron nitride, which can stably exist at normal temperature and pressure.
[0024] In some embodiments, the pressurization treatment time is 1-10 seconds, so that the hexagonal boron nitride is converted into wurtzite boron nitride.
[0025] In some embodiments, the mass number of boron in the hexagonal boron nitride is 10 and / or 11. The boron element includes two isotopes, and the raw material in the present application can be boron 10 and / or boron 11. The proportions of boron 11 and boron 10 are different, and the thermal conductivity of the material is different, which can be selected as needed.
[0026] According to an embodiment of the present application, a wurtzite boron nitride prepared by the preparation method described in any embodiment of the present application is also provided. The wurtzite boron nitride prepared in the present application has a stable WBN phase. The corresponding pressure conditions can be selected for preparation according to the thermal conductivity requirements and the content requirements of the WBN phase.
[0027] According to an embodiment of the present application, a method for regulating the thermal conductivity of boron nitride is also provided, wherein hexagonal boron nitride is treated at room temperature and pressurized conditions using a diamond anvil cell to obtain a boron nitride product; by regulating the pressurized pressure, boron nitride with different thermal conductivities and different crystal phases is obtained, and the pressurized pressure is 0-50 GPa.
[0028] Pure hexagonal boron nitride, hexagonal boron nitride and WBN boron nitride, and pure WBN boron nitride can be prepared under different pressure conditions. Different thermal conductivities can also be obtained to be suitable for electronic devices with different heat dissipation efficiencies.
[0029] Example 1 The mechanical stripping method was used to obtain a sheet material with an irregular shape of 40-60μm and a thickness of 67nm. Based on the two-dimensional transfer platform, the sample was cleanly and point-to-point transferred to the diamond table in the DAC device. The diamond anvil device was placed in a magnetron coating instrument to control the coating rate to achieve a 65nm gold film coverage. A ruby ball was inserted with a needle tip for in-situ pressure monitoring, and silicone oil was sealed in the chamber so that the inside of the chamber met the hydrostatic pressure pressurization requirements. The hexagonal wrench was rotated by both hands at the same time to apply pressure, rotating 30-60° each time, and then the screws on the adjacent two sides were replaced, and the same angle was repeatedly rotated to apply pressure. The product was obtained by reacting for 5s at each pressure, and the boron nitride of each phase in the obtained product remained stable.
[0030] The Raman real-time detection method is used to determine the changes in boron nitride under various pressures. The specific method is as follows: Raman real-time in-situ detection of samples and ruby balls to monitor the pressure, and the time at each pressure is maintained for 35 minutes for Raman detection.
[0031] Raman spectroscopy was used to detect the boron nitride products corresponding to the untreated hexagonal boron nitride raw material, 0.7 GPa, 1.77 GPa, 1.98 GPa, 3.79 GPa, 5.36 GPa, 9.25 GPa, 9.72 GPa, 12.16 GPa, 13.11 GPa, 13.32 GPa, 14.30 GPa, 15.56 GPa, and 16.74 GPa conditions, and the results were as follows: Figure 1 and Figure 2 As shown, Figure 1 The AP curve in the middle represents the result of Raman spectroscopy detection of hexagonal boron nitride at normal pressure before the reaction.
[0032] pass Figure 1 It can be found that under the condition of 9.25 GPa, hexagonal boron nitride still exists, and under the condition of 13.32 GPa, there is still a small amount of hexagonal boron nitride.
[0033] pass Figure 2 It can be seen that the hexagonal boron nitride in the product obtained under the condition of 12.16 GPa is significantly reduced, and the product obtained under the condition of 15.56 GPa is completely wurtzite boron nitride. The product obtained under the condition of 16.74 GPa is completely wurtzite boron nitride.
[0034] pass Figure 1 and Figure 2 It can be found that during the pressure increase process, the crystal phase of boron nitride changes.
[0035] like Figure 3 As shown in the figure, after the pressure was increased to 16.74 GPa, the Raman spectrum of the product was detected during the process of decompression to normal pressure. It can be found that the 1358 cm-1 No peak appears at the position, indicating that after the pressure is released, there is only wurtzite boron nitride in the product, and no hexagonal boron nitride, indicating that wurtzite boron nitride that is stable at room temperature and pressure has been prepared.
[0036] The raw material in Example 1 is boron nitride enriched with B11 (the mass number of boron is 11), such as Figure 4 The following are the Raman spectra of boron nitride with different mass numbers. Figure 4 As shown, the purple line has the highest B11 content, greater than 99%, and the black line is the hBN boron nitride raw material of Example 1. From left to right, B11 gradually decreases, and B10 gradually increases. Figure 4 It can be seen that the hBN peak in the hBN boron nitride raw material of Example 1 is located at 1358 cm -1 Nearby location.
[0037] Example 2 The mechanical stripping method was used to obtain a sheet material with an irregular shape of 40-60μm and a thickness of 67nm. Based on the two-dimensional transfer platform, the sample was cleanly and fixedly transferred to the diamond table in the DAC device. The diamond anvil device was placed in the magnetron coating instrument to control the coating rate to achieve 65nm gold film coverage. A ruby ball was inserted with a needle tip for in-situ pressure monitoring, and silicone oil was sealed in the chamber so that the inside of the chamber met the hydrostatic pressure pressure requirements. The hexagonal wrench was rotated by both hands at the same time to apply pressure, 30-60° each time, and then the screws on the adjacent two sides were replaced, and the same angle was repeatedly rotated to apply pressure. Raman was used to detect the sample and the ruby ball in real time in situ to monitor the pressure, increase it to different pressures, and keep it at the corresponding pressure for 30 minutes for thermal conductivity detection.
[0038] The pressures are 2.6 GPa, 3 GPa, 7.5 GPa, 11 GPa, 13 GPa, 16 GPa, and 22 GPa. The thermal conductivity of boron nitride under different pressure conditions was tested using the TDTR method (time domain thermal reflection measurement system). The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the thermal conductivity increases during the pressure increase process, and after the WBN phase is transformed, the thermal conductivity decreases. Therefore, the method for preparing wurtzite boron nitride using a diamond anvil cell in the present application can obtain boron nitride products with different thermal conductivities and different crystal phases by adjusting the conditions, thereby realizing the design of the thermal conductivity and crystal phase of boron nitride.
[0039] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.
[0040] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.
[0041] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
Claims
1. A method for preparing wurtzite boron nitride, characterized in that: The preparation method comprises: using a diamond anvil cell device, taking hexagonal boron nitride as a raw material, and preparing wurtzite boron nitride under normal temperature and pressurized conditions, wherein the pressurized pressure is greater than or equal to 12 GPa.
2. The preparation method according to claim 1, characterized in that: The pressurized pressure is greater than or equal to 15 GPa.
3. The preparation method according to claim 1, characterized in that: The preparation method further comprises: plating a gold film on the surface of the hexagonal boron nitride, and placing the gold-plated sample into a chamber of a diamond anvil device and then subjecting it to a pressurization treatment.
4. The preparation method according to claim 1, characterized in that: The pressure is applied by rotating the diamond anvil, with each rotation angle being 30-60°.
5. The preparation method according to claim 1, characterized in that: The thickness of the hexagonal boron nitride raw material is 60-80 nm.
6. The preparation method according to claim 1, characterized in that: The thickness of the covering gold film is 60-80 nm.
7. The preparation method according to claim 2, characterized in that: After the pressure treatment, the diamond anvil cell is depressurized to obtain wurtzite boron nitride.
8. The preparation method according to claim 1, characterized in that: The mass number of boron in the hexagonal boron nitride is 10 and / or 11.
9. Wurtzite-type boron nitride prepared by the preparation method according to any one of claims 1 to 9.
10. A method for regulating the thermal conductivity of boron nitride, characterized in that: The hexagonal boron nitride is treated at room temperature and under pressure using a diamond anvil cell to obtain a boron nitride product; by adjusting the pressure of the pressurization, boron nitride with different thermal conductivities and different crystal phases is obtained, and the pressurization pressure is 0-50 GPa.
Citation Information
Patent Citations
High-pressure technology for low-temperature polymerization and rapid non-crystallization of C60
CN106622034A
Visual and controllable pressurization system based on diamond anvil cell and use method of visual and controllable pressurization system
CN116832702A
Superhard wrinkled nano polycrystalline wurtzite type boron nitride material and preparation method thereof
CN117466260A
Synthesis process of high-purity diamond alkene transistor
CN118315275A
Improvements in boron nitride and methods of production relating thereto
GB1048973A
Cited By
Wurtzite boron nitride / diamond composite material and preparation method and application thereof
CN121948978A
